The Evolution of the Heart Transplant Surgical Technique - Mehmet H. Akay; Erik E. Suarez; O. H. Frazier (Methodist DeBakey Cardiovascular Journal)
This overview of the history of human cardiac transplant shares detailed illustrations to demonstrate how surgical procedures have improved since the first human transplant was performed in 1967 in Cape Town, South Africa.